PALM OIL EPOXIDATION BY V2O5 / ?-AL2O3 - Kartika Salduna, Eunike
European countries recently reduced the use of phthalates as plasticizers because of their toxicity. Vegetable oil epoxides were reported as alternative plasticizers with nontoxic and benign properties. Palm oil epoxide (epoxidized palm oil or EPO) shows and is produced by oxidizing triglyceride olefins using H2O2 and acids. However, the process releases heat that is relatively hard to control, corrosive, and may decrease the selectivity of epoxides because of further hydrolysis of epoxide rings. The oxidation reaction of palm oil in this study used tertiary-butyl hydrogen peroxide or TBHP as an oxidizing agent, assisted by V2O5/?-Al2O3 (1 : 10 mol). The support of ?-Al2O3 was chosen because it may deposit vanadia while providing ease process of catalyst regenerations. The regeneration of unsupported-V2O5 from palm oil is relatively difficult. Synthesis of V2O5/?-Al2O3 is carried out by dropwise impregnation of alumina by a solution of VO(acac)2 complex followed by heating at 100 ?C (2 h) and calcination at 500 ?C (5 h). Catalytic reaction tests were also conducted with various types of 1st raw transition metal oxides, impregnated on alumina (Cr2O5, CuO, Fe2O3, NiO) to evaluate the oxide character. The observation showed excellent epoxidation on V2O5/?-Al2O3 employmentresults compared to other oxides. Optimized reaction conditions were achieved at 80 ?C, 7 h, 0.5 mol% of vanadium upon olefins, and 3.5 mol eq. of TBHP. A longer reaction indicated the opening of epoxide rings. A kinetics study showed that the reaction was a pseudo- 2nd order upon palm oil with an activation energy (Ea) of 27 kJ?mol?1, turn over number (TON) of 138 and turn over frequency (TOF) of 20 h?1. Such an activation energy is lower than the reported uncatalyzed-reaction (Ea of 91 kJ?mol-1). The catalytic study also described transition state values of free Gibbs energy (?G‡) of 90 kJ?mol?1, entropy (?S‡) of ?188 J?mol?1?K-1 , and enthalpy (?H‡) of 24 kJ?mol?1. Recycling of V2O5/?-Al2O3 catalysts was carried out by ethanol rinsing and drying at 80 ?C (1 h). Recycled-catalyst gave relatively good epoxidized oil (up to 75% PO conversion). Epoxidation of waste-cooking oil (WCO) resulted in epoxidized WCO of 50% PO conversion .